Intravenous fluids: effects on renal outcomes. (February 2018) - McLean, D.J.; Shaw, A.D.
Abstract: Intravenous fluid therapy is the most commonly prescribed inpatient medication in hospitals around the world. Intravenous fluids are drugs and have an indication, a dose, and expected and unintended effects. The type and amount of fluid given to patients are both important, and can either hasten or slow recovery depending on how they are administered. This narrative review provides a brief summary of the effect of intravenous fluid administration on kidney function and on renal outcome measures of relevance to both patients and clinicians. Several large clinical trials of fluid therapy are currently underway, the results of which are likely to change clinical practice.